الواقـع والرؤيا عند محمود درويش قراءة في جدارية محمود درويش - كلفالي, سميحة (قــــــراءات, 2019)
تهدف هذه الدراسة للكشف عن العلاقة بين الرؤيا والواقع عند الشاعر الفلسطيني محمود درويش، خاصـة أن كثيرا من الشعـراء المعاصرين قد أوغـلوا في التجريد، في حين أن الشاعر محمود درويش قد انطلق من واقعـه -واقع فلسطين المحتلة- إيمانا منه بأنه المنطلق للتغيير والتحرر، فهو البوابة التي تصل بالعالم الآخر.   Abstract : The aim of this study is to show the relationship between vision and reality for the Palestenian poet “Mahmoud Darwish”. We will focus on this poet in particular because many contemporary poets got deep in the abstraction whereas “Mahmoud Darwish” started from his own reality. The reality of the occupied Palestine believing that it should be the basis of change and liberation. He is the bridge that connects Palestine to the outside world.